The epithelial sodium channel in inflammation and blood pressure modulation - Ahmad, Taseer; Ertuglu, Lale A.; Masenga, Sepiso K.; Kleyman, Thomas R.; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2023)
A major regulator of blood pressure and volume homeostasis in the kidney is the epithelial sodium channel (ENaC). ENaC is composed of alpha(α)/beta(β)/gamma(γ) or delta(δ)/beta(β)/gamma(γ) subunits. The δ subunit is functional in the guinea pig, but not in routinely used experimental rodent models including rat or mouse, and thus remains the least understood of the four subunits. While the δ subunit is poorly expressed in the human kidney, we recently found that its gene variants are associated with blood pressure and kidney function. The δ subunit is expressed in the human vasculature where it may influence vascular function. Moreover, we recently found that the δ subunit is also expressed human antigen presenting cells (APCs). Our studies indicate that extracellular Na+ enters APCs via ENaC leading to inflammation and salt-induced hypertension. In this review, we highlight recent findings on the role of extra-renal ENaC in inflammation, vascular dysfunction, and blood pressure modulation. Targeting extra-renal ENaC may provide new drug therapies for salt-induced hypertension.